Investigation of laser-induced plasma evolution in flexible pad laser shock forming with high speed camera - Nagarajan, Balasubramanian (2015)
This study investigated the effect of plasma evolution, which dominates the forming load, on the fabrication of microcraters in flexible pad laser shock forming (FPLSF) using a high speed camera. It has been found that the plasma lifetime starting from plasma formation, expansion, decaying to vanishing was less than 13.3 us at single pulse ablation, 350 times longer than the pulse duration. When 45 pulses were applied as 5 cycles with 9 pulse train in each, the plasma size increased gradually to its maximum at the fifth or sixth pulse. There was no interference between the plasma generated from each pulse. The first pulse was sufficient for the fabrication of a crater. The crater depth and diameter increased only by 10% and 25% respectively at ablation with 45 pulses. At 45 pulses ablation for fluence from 7.3 J/cm2 to 20.9 J/cm2 in water confinement, the change factor appeared in descending sequence from laser fluence, maximum plasma diameter, maximum plasma pressure, to crater depth by the order of 2.86, 2.18, 1.69 and 1.47 respectively. In glass, the plasma diameter increased by 3.28 times at increasing laser fluence. The confined plasma in glass resulted in deeper craters. The smaller craters in water were attributed to the forming load diminution due to the plasma expansion, shockwave attenuation in ablative overlay, and the laser energy reduction.